A common solution of f-fixed point and variational inequality problems in Banach spaces. (4th March 2023) - Zegeye, Habtu; Boikanyo, Oganeditse A.
ABSTRACT: In this paper, we construct a Halpern-type subgradient extragradient iterative algorithm which converges strongly to a common point of the f -fixed point set of a continuous f -pseudocontractive mapping and the solutions set of a variational inequality problem for Lipschitz monotone mapping in reflexive real Banach spaces. In addition, a numerical example is given to demonstrate the behaviour of the convergence of the algorithm. Our results improve, generalize and unify some related recent results in the literature.